STEREOTYPES AND FEMINISM IN THE MOVIE MULAN BY WALT DISNEY - Alfa Selkli Indira Supit; Kristin Marwinda (LINGUAMEDIA Journal, 2021)
The topic of this paper is the relationship between feminism and the stereotypes in the movie Mulan by Walt Disney (1998). Mulan is the representation of a tough and brave woman. The movie raises the issue of Mulan’s feminism as the main character and gender stereotype that suggests women as inferior to men. This paper focuses on the main character and how she tries to break the stereotypes in her society. Liberal feminist theory is used as an approach in this paper. The sources to conduct the analysis are journals, articles, books, and the internet. The result of the analysis shows that women can also participate in public and society when they are given the same opportunity as men have. Keywords: feminism, stereotypes, liberal feminist, public places